2001
DOI: 10.1046/j.1365-2591.2001.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of specialty training and experience on decision making in endodontic diagnosis and treatment planning

Abstract: Differences in specialty backgrounds amongst the participants in this study affected both endodontic diagnostic and treatment decisions. Endodontists showed the most consistent agreement amongst the specialty groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 17 publications
6
54
1
2
Order By: Relevance
“…A previous study showed no significant difference between bleaching efficacy when the home bleaching technique was performed alone or combined with in-office treatment (4). There is also a tendency for increased tooth sensitivity when high concentration agents are used (5,25,14).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed no significant difference between bleaching efficacy when the home bleaching technique was performed alone or combined with in-office treatment (4). There is also a tendency for increased tooth sensitivity when high concentration agents are used (5,25,14).…”
Section: Discussionmentioning
confidence: 99%
“…Because endodontists have at least two additional years of specialty training following graduation from dental school with a broader and deeper body of knowledge, this difference probably explains why so many GDPs are less consistent with RD application. 27,28 The main reasons for the negative opinion of GDPs towards RD application are difficult placement, time required for application, occasional patient complaints and cost. 8,10,15,29 In an attempt to overcome these drawbacks, other isolation techniques have been undertaken by GDPs during root canal treatment.…”
Section: Factors Affecting Rubber Dam Use After Graduationmentioning
confidence: 99%
“…1 The decisionmaking process for the restoration or the replacement of teeth is complex. 2 Attempts have been made to rationalise the process and strategies have been devised to guide less experienced clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…2 Attempts have been made to rationalise the process and strategies have been devised to guide less experienced clinicians. 1,[3][4][5][6] Aims This study was designed to determine the effect of reflection and discussion of a group of dentists with differing backgrounds and qualifications in the management of failed endodontic treatment. Materials and methods During the Dental Pan-Society plenary session (16-17 November 2007) delegates (n = 393) were asked a series of questions on the management of a case with failed endodontic treatment of four maxillary incisors restored with linked crowns in a patient with a high smile line.…”
Section: Introductionmentioning
confidence: 99%